A PjBL-Based Student Worksheet on Integers to Support the Numeracy Skills of Grade VII Learners - Rosyida, Luluk; Rejeki, Sri; Setyaningsih, Rini (Urogram Studi Pendidikan Matematika, Universitas Ivet, 2024)
This research is about the development of a PjBL-based student worksheet that aims to support the numeracy skills of students, especially at the junior high school level, and to describe the development process as well as the validity and feasibility of PjBL-based student worksheet on the topic of integers to support the numeracy skills of seventh-grade students. This research uses the ADDIE development model (Analyze, Design, Development, Implementation, evaluation). The development stages in this research are preliminary studies, planning, worksheet development, worksheet validation, and worksheet feasibility testing. The subjects of this study were seventh-grade students of a private junior high school in Surakarta, Central Java, Indonesia, in the 2023/2024 academic year. The data obtained from this study were interviews and questionnaire assessments. The worksheet validation by two expert validators showed that the worksheet was declared very valid with an average score of 3.725. The feasibility test results based on a questionnaire from students showed an average score of 3.248 with a very valid category.